On the Measurement of Excess Capacity in Retailing - Holton, Richard H. (Review of Economic Studies, 1956)
Journal Article On the Measurement of Excess Capacity in Retailing Get access Richard H. Holton Richard H. Holton Cambridge, Mass. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 24, Issue 1, 1956, Pages 43–48, https://doi.org/10.2307/2296235 Published: 01 July 1956